Market reforms in the French healthcare system: between regulation and yardstick competition. Issue 3 (3rd April 2022) - Simonet, Daniel; Katsos, John E.
IMPACT: Responding to New Public Management reforms, the French healthcare system adapted by creating a hybrid model. This paper details those reforms, their hybridity, and their applicability in other contexts.